2007
DOI: 10.1039/b603256g
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic ion channels in bilayer membranes

Abstract: Natural ion channels are large protein complexes that regulate key functions of cells. Supramolecular chemists have been able to take hints from Nature to design and prepare completely synthetic ion channel systems that reproduce many of the fundamental functions of natural channels. This tutorial review introduces the field to non-specialists. It examines the design, synthesis, incorporation, and characterization of synthetic ion channels in bilayer membranes, and points to potential applications of synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
175
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(176 citation statements)
references
References 33 publications
0
175
0
1
Order By: Relevance
“…Excellent reviews continuously update this field from different points of view. [49][50][51][52][53][54][55][56][57] Specific topics of current interest that became accessible with the introduction of rigid-rod scaffolds include ion selectivity, voltage gating, membrane recognition, ligand gating, blockage, and catalysis. 12 Rigid O-NDI rods 6 ( Fig.…”
Section: Ion Channels and Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent reviews continuously update this field from different points of view. [49][50][51][52][53][54][55][56][57] Specific topics of current interest that became accessible with the introduction of rigid-rod scaffolds include ion selectivity, voltage gating, membrane recognition, ligand gating, blockage, and catalysis. 12 Rigid O-NDI rods 6 ( Fig.…”
Section: Ion Channels and Poresmentioning
confidence: 99%
“…33 However, cation-interactions are intrinsic characteristics of -basic aromatics and thus ubiquitous in natural and synthetic multifunctional architecture. In clear contrast, anion-interactions are theoretically attractive, 54 poorly explored in solution, 55 without reach with biological ion channels and unprecedented in synthetic ion channels. [49][50][51][52][53][54][55][56][57] Our high-level DFT calculations suggested that the global quadrupole moment of the -acidic…”
Section: Ion Channels and Poresmentioning
confidence: 99%
“…Many synthetic supramolecular systems capable of physically transporting chemical signals, such as ions, across lipid bilayer membranes have been reported. [3][4][5][6][7][8][9] However, mimicking signal transduction and amplification processes that occur without physical transfer of matter has proved a considerable challenge for synthetic systems. [10][11][12][13][14][15] Recently, we have shown that a new abiotic mechanism -membrane translocation -can be used for signal transduction across lipid bilayers in artificial systems ( Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, a rich variety of novel artificial nanochannels have been constructed, which is attracting widespread interest because their potential applications in biosensors, drug delivery, nanofluidic devices, etc. 4,5 Experimentally, the integration of stimuli responsive polyelectrolyte brushes into solid-state single nanochannels can create tailor-made nanovalves resembling the functions of sophisticated biological ion channels. 6 The gating mechanism is implemented by collapse-stretching conformational transition of the brushes responsive to pH.…”
Section: Introductionmentioning
confidence: 99%